A Colonial and Post-Colonial Assessment of Language in Akespear’s the Tempest and Friel’s Translations - Ashkoor, Maryam Ataollahi (2008)
This study examines the significance of language in connection with both personal and national identity. Language and identity have a power to fix thoughts and beings. It roots a nation to a past. Language bridges between a contemporary society and its dead ancestors. Language contains elements of culture, human interaction, environment, working of the human brain and identity. People are marked by the language that they speak. Britannia recognized this significance. Therefore, it could have power not necessarily through physical control but mental control as well. It could change the colonized countries into mimic people who just copy British values, cultures, beliefs, and identities. First, through establishing binary oppositions, Britannia began to justify its settlement in the natives’ lands and Ireland. In Shakespeare’s The Tempest, binarism emerged as lack of moral sense/ moral sense or good/evil and savage/civilized. Prospero introduced herself as a man who is civilized and moral whereas, Caliban is a native who is a barber and has no moral sense. Education was exercised through language. Therefore, Prospero introduced himself as a compassionate “schoolmaster” who had a burden to teach Caliban his language. Under Prospero’s education, Caliban loses his identity. He loses his freedom and changes into a slave that Prospero dares even to insult but in Friel’s Translations, binarism emerged as modern/archaic and standard/nonstandard. Britannia introduced its National schools which are modern, advanced, and new whereas, Hedge schools were traditional and archaic. They also claimed that Irish lands were not standard, without boundaries and map whereas, English villages, towns, and cities were mapped and standard. They introduced themselves as compassionate teachers and cartographers who attempted to modernize and standardize Irish schools and lands. Second, by comparing and contrasting Shakespeare’s The Tempest and Friel’s Translations from different periods, the process of imperial justifications are disclosed. This study presents that Britannia adopted imperial justifications in accordance with the situations and necessities. For instance, Caliban’s situation differs from the Irish. Prospero in The Tempest could introduce Caliban as a savage but Britannia could not claim that the Irish were savages like the natives in the New World. Third, they disguised their justifications in accordance with modernization and standardization. However, imperial justifications differed from period to period with language playing the main role for all of them. Teaching, mapping, christinizing modernizing, and standardizing relied on language. In this study, language is the base for imperial superstructures (justifications). Fourth, this study discusses that a person loses his language; he will change into a mimic character. He forgets his essence, values, cultures, and identity. In The Tempest, losing identity is depicted through humiliation and demoralization as Prospero has nothing for Caliban but nasty words. In Translations, it is depicted through mimicry.